Prenatal diagnosis of harlequin ichthyosis. Case report - Reyna-Villasmil, Eduardo (2023)
Harlequin ichthyosis, also known as diffuse fetal keratosis, is an extremely rare andphenotypically severe hereditary skin disorder with autosomal recessive inheritance.This disease is caused by mutations in the adenosine triphosphate-binding cassettetransporter protein (ABCA12) gene. Prenatal ultrasonography and genetic analysisare important for prenatal diagnosis. Prenatal ultrasonographic diagnosis is difficult,and findings include ectropion plates, an abnormal auricular pinna, a flat nose,thickened skin with an armor-like appearance, thickened lips with sustained openmouth (fish mouth) status, and flexion fixation of the extremities. These are usuallyfound during the third trimester. Three-dimensional ultrasonography contributesto the evaluation of facial morphology. The prognosis is generally poor. Affectedneonates usually do not survive beyond the first days of life. A case of prenataldiagnosis of harlequin ichthyosis is presented.